Resilience of Small Ruminants to Climate Change and Increased Environmental Temperature: A Review - Aleena Joy (Animals, 2020)
Climate change is a major global threat to the sustainability of livestock systems. Climatic factors such as ambient temperature, relative humidity, direct and indirect solar radiation and wind speed influence feed and water availability, fodder quality and disease occurrence, with production being most efficient in optimal environmental conditions. Among these climatic variables, ambient temperature fluctuations have the most impact on livestock production and animal welfare. Continuous exposure of the animals to heat stress compromises growth, milk and meat production and reproduction. The capacity of an animal to mitigate effects of increased environmental temperature, without progressing into stress response, differs within and between species. Comparatively, small ruminants are better adapted to hot environments than large ruminants and have better ability to survive, produce and reproduce in harsh climatic regions. Nevertheless, the physiological and behavioral changes in response to hot environments affect small ruminant production. It has been found that tropical breeds are more adaptive to hot climates than high-producing temperate breeds. The growing body of knowledge on the negative impact of heat stress on small ruminant production and welfare will assist in the development of suitable strategies to mitigate heat stress. Selection of thermotolerant breeds, through identification of genetic traits for adaption to extreme environmental conditions (high temperature, feed scarcity, water scarcity), is a viable strategy to combat climate change and minimize the impact on small ruminant production and welfare. This review highlights such adaption within and among different breeds of small ruminants challenged by heat stress.